Educating the Intellect without a Teacher: The Concept of Independent Learning in the Philosophy of Islamic Education in Hayy bin Yaqdzon by Ibnu Thufail - Tuti Mayukha; Mutohharun Jinan; M.A. Fattah Santoso (Universitas Muhammadiyah Surakarta, 2025)
This paper examines the thoughts of Ibn Thufail's Islamic educational philosophy through his monumental work Hayy Ibn Yaqdzan. The purpose of this paper is to understand the background of Ibn Thufail's life and intellectual journey, to describe the main ideas in the story of Hayy Ibn Yaqdzan, and to analyze the relevance of the concept of Islamic educational philosophy contained therein to the development of science and education today. This study uses a qualitative approach with a library research method. Data were obtained from the primary work of Ibn Thufail Hayy Ibn Yaqdzan and various secondary sources in the form of books, scientific journals, and relevant literature. The data analysis technique was descriptive-analytical, namely by describing the content of the text and then analyzing it philosophically and educationally. The results of the study show that the philosophy of Islamic education in the story of Hayy Ibn Yaqdzan emphasizes the importance of the natural and potential of human reason, nature as a source and medium of learning, education through experience and reflection, stages of intellectual and spiritual development, independent learning, and harmony between reason and revelation. The ultimate goal of Islamic education according to Ibnu Thufail is the achievement of ma'rifatullah and the formation of human beings who are knowledgeable, faithful and have noble character. Ibn Thufail's thoughts remain relevant as a basis for developing holistic and humanistic Islamic education in the modern era.